Structural And Optical Properties Of Sputtered Nanocrystalline Indium Nitride On Silicon Substrates - Amirhoseiny, Maryam (2013)
The aim of this project is to study the growth and characterization of nanocrystalline indium nitride (InN) on silicon (Si) substrates by means of various non-contact and non-destructive characterization tools. These include the scanning electron microscopy (SEM), energy dispersive X-ray (EDX) analysis, atomic force microscopy (AFM), and X-ray diffraction (XRD) for structural characterization, and Fourier transform infrared (FTIR) spectroscopy, micro-Raman spectroscopy, and photoluminescence (PL) spectroscopy for optical characterization. Initial works on the structural and optical characterization of the nanocrystalline InN grown on anisotropic (110) orientation of sillicon (Si) substrates have been carried out. Studies are, however, focused on optimizing the deposition conditions for growing nanocrystalline InN by radio frequency (RF) sputtering method. All deposited films obtained under different deposition conditions were slightly nitrogen-rich, but increasing the RF power provided more InN compounds in stoichiometric form. XRD results revealed wurtzite nanocrystalline InN films with a (101) preferred growth orientation for all deposited films. The strong PL peak was observed in the energy of 1.9 eV at room temperature. This higher value of the bandgap is due to the Moss–Burstein shift effect.